THU0398 GAIT 3D KINEMATICS UNVEILS A SPECIFIC PATTERN IN PATIENTSIN EARLY YEARS OF AXIAL SPONDYLOARTHRITIS INDEPENDENT OF THEIR BODY COMPOSITION AND MUSCLE PERFORMANCE VARIABLES. (June 2019) - Santos, Fernando Pimentel dos; Domingues, Lucia; Mendes, César; Matias, Ricardo; Rodrigues-Manica, Santiago; Crespo, Carolina; Branco, Jaime
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic disease characterized by a progressive mobility reduction of the rachis. The postural changes may cause balance problems with gait repercussions. However, we lack information during the early years of the disease regarding gait pattern and the possible variables that may influence gait parameters. Objectives: In order to gain insight into the gait patterns in patients at early stages of axSpA and the potential influence of some patient-specific features, the aim of this study was therefore to evaluate: (i) the 3D gait signature in patients at early years of axSpA; and (ii) the relation between gait parameters, and body composition and muscle performance variables. Methods: A cross-sectional study was conducted on 46 participants (18-50 years old), 23 patients with axSpA (according to ASAS criteria, with less than 10 years since symptoms onset) and 23 healthy controls, matched by gender and age, with a mean age of 37±7.5 years, predominantly males (60%). The patients with axSpA had 5±3.2 years of disease duration, with BASDAI and BASFI of 3±2.2 and 2±2.9, respectively. Subjects' movement was reconstructed using a 3D full-body kinematic model (Kinetikos, Coimbra, Portugal) fed by 15 inertial sensors placed in the head, arms, trunk, pelvis, thighs, shanks and feet. The primary outcomes comprise the general gait parameters such as gait deviation index, speed, cadence, stance duration, body vertical regularity (sample entropy), step length, range of movement and peak velocity of the different joints. Body composition was assessed by performing octapolar multifrequency bioelectrical impedance analysis (BIA; InBody 770). Muscle performance was assessed with a 60 second sit-to-stand test (STS60), while physical activity was controlled by the international physical activity questionnaire (IPAQ). Variables (except age, disease duration, BASDAI, BASFI) are presented as median. Non-parametric tests were used to compare groups. Correlations between gait, body composition and skeletal muscle function parameters, were performed. Results: Gait analysis showed statistically significant differences between axSpA and healthy control groups on gait deviation index (median 83 vs 87%, p=0.022, with higher score values representing similar performance to normal movement), speed (median 0.79 vs 0.85m/s, p=0.015), stance duration at the left side (median 68 vs 67s, p=0.027), left step length (median 0.47 vs 0.49m, p=0.008), and vertical regularity (median 0.39 vs 0.33, p=0.029, with higher values representing a less regular and predictable movement pattern). At the sagittal plane, patients showed higher values of left arm maximum flexion (median 14 vs 10°, p=0.011), lower lumbar extension peak velocity (median 45 vs 60°/s, p=0.016) and higher ankle angular peak velocity on right side (median 330 vs 299°/s, p=0.020). However, no statistically significant differences between groups were found for physical activity. In addition, no statistically significant correlation was found between the gait parameters and weight, body fat, torso fat, visceral fat, body mass index, total body water, extracellular water, fat free mass, lean mass, bone mineral content and STS60. Conclusion: These results provide evidence that although young axSpA patients at early years of the disease display a particular gait pattern and this behavior does not seem to be influenced by the body composition and muscle performance. The main determinant for this gait pattern remains an open question. Disclosure of Interests: Fernando Pimentel dos Santos Grant/research support from: From Abbvie and Novartis, Speakers bureau: Abbvie, Novartis, Pfizer, Biogen, Lucia Domingues: None declared, César Mendes: None declared, Ricardo Matias: None declared, Santiago Rodrigues-Manica: None declared, Carolina Crespo: None declared, Jaime Branco: None declared